Implementasi Kebijakan Peraturan Walikota No. 49 Tahun 2021 di Kota Medan - Ijan Paulinus Sijabat; Yusniar Lubis; Budi Hartono (Mahesa Research Center, 2023)
The purpose of this research is to analyze the implementation and identify the factors that influence the Implementation of the Medan Mayor Regulation Number 49 of 2021 Concerning Competency Development of State Civil Servants in the Medan City Government in the Planning and Finance Section of the Medan City Regional Secretariat. This study applies Edward III's Theory. This research use desciptive qualitative approach. The informants in this study were the Head of the Planning and Finance Section of the Medan City Regional Secretariat, the Planning Sub-Coordinator, the Finance Sub-Coordinator, and the Reporting Sub-Coordinator. Data collection techniques in this study were observation, interviews, and documentation. The data analysis technique in this research uses the theory of Miles and Huberman. The results of the study show that the Implementation of the Policy for Medan Mayor Regulation Number 49 of 2021 Concerning the Competency Development of State Civil Servants in the Medan City Government in the Planning and Finance Section of the Medan City Regional Secretariat has gone well but there are still deficiencies, namely in the aspect of resources. The factors that influence implementation are supporting factors in the form of channeling information by sending letters done clearly and consistently, as well as inhibiting factors in the form of unenthusiastic human resources, limited budgets, facilities where they are still renting, and limited authority.